Simultaneous observations of spread F irregularities over Southeast Asia longitude using Sanya VHF radar, GPS and C/NOFS. Issue 7 (1st April 2019) - Meng, Xing; Fang, Hanxian; Weng, Libin; Liu, Zhendi
Abstract: Through concurrently measurements by Communication/Navigation Outage Forecasting System (C/NOFS), Sanya VHF radar and GPS ionospheric scintillation receiver on 12 March 2010, five plasma bubbles were found and three of them were observed by all those instruments. Two well-developed plumes with strong backscatter echoes were measured by Sanya radar and their corresponding depletions were observed by C/NOFS in Orbit 10317, 10318 and 10319. Broad plasma depletions resulting from merging process were found in orbit of 10318. The occurrence time and geophysical positions of scintillations correlate well with observations implemented by Sanya VHF radar and C/NOFS. Observations from three types of instrument indicate that the spread F irregularities have distinct scale. There were longitudinal differences between Sanya VHF radar and C/NOFS as irregularities measured, and the eastward drift of developed bubbles are responsible for these differences.